Resistance mutations of hepatitis B virus in entecavir‐refractory patients. Issue 2 (9th March 2017) - Yamada, Norie; Sugiyama, Ryuichi; Nitta, Sayuri; Murayama, Asako; Kobayashi, Minoru; Okuse, Chiaki; Suzuki, Michihiro; Yasuda, Kiyomi; Yotsuyanagi, Hiroshi; Moriya, Kyoji; Koike, Kazuhiko; Wakita, Takaji; et al.
Abstract : The emergence of resistance mutations in the reverse transcriptase gene of hepatitis B virus (HBV) is associated with treatment failure. Entecavir (ETV) is one of the most potent anti‐HBV reagents; it has a very low resistance rate and is used as the first‐line treatment for chronic hepatitis B. In this study, we isolated HBVs in 4 ETV‐refractory patients (2 with viral breakthrough, 1 with partial virological response, and 1 with flare‐up) and assessed ETV resistance using replication‐competent 1.38‐fold HBV genome‐length molecular clones. The full genome sequences of infected HBVs in ETV‐refractory patients were determined. The HBV molecular clones were generated with the patient‐derived sequences. After transfection of these molecular clones into HepG2 cells, viral replications and ETV susceptibilities were evaluated by measuring the amount of intracellular core‐particle‐associated HBV DNA using Southern blotting and real‐time polymerase chain reaction. Among these cases, ETV‐resistant variants were detected in 2 patients with viral breakthrough and responsible amino acid mutations in reverse transcriptase were successfully identified in these variants. No ETV‐resistant mutation was detected in the other cases. The identified ETV‐resistant mutations did not confer resistance to tenofovir disoproxil fumarate. Conclusion : The HBV replication model with patient‐derived sequences is useful for assessing replication efficiency, susceptibility to anti‐HBV reagents, and responsible resistance mutations and can aid in choosing the appropriate treatment strategy for treatment‐failure cases of chronic hepatitis B. ( Hepatology Communications 2017;1:110‐121)